Evolution of the essential gene MN1 during the macroevolutionary transition toward patterning the vertebrate hindbrain - Elio Escamilla-Vega; Louk W. G. Seton; Stella Kyomen; Andrea P. Murillo-Rincón; Julian Petersen; Diethard Tautz; Markéta Kaucká (Proceedings of the National Academy of Sciences, 2025)
The tight link between brain and skull formation is a fundamental aspect of vertebrate evolution and embryogenesis. Their developmental synchronization is essential for structural and functional integration. The brain and skull shape coevolution is evident along the vertebrate phylogeny; however, the genetic basis underlying their close evolutionary and developmental relationship remains little explored. Here, we reveal the evolution and function of the MN1 gene that was previously found to be associated with significant shape variation in the mouse skull and the formation of cranial bones. We show that the vertebrate MN1 gene evolved from an ancestral deuterostome sequence. In vertebrates, the MN1 gene structure, synteny, and spatiotemporal expression pattern are remarkably conserved, indicating that the gene carries out a core function. Using a newly generated mouse knock-out model, we demonstrate in vivo that Mn1 integrated into an ancient molecular machinery and controls the expression of the Cyp26 genes in the developing hindbrain, thereby tuning the retinoic acid levels and patterning of the developing central nervous system. This study thus showcases the emergence of a novel gene function from an ancestral sequence and its role in generating a macroevolutionary innovation. The data expand our knowledge of brain and skull codevelopment and coevolution and highlight the role of this regulatory loop in craniofacial human syndromes.